Neuroprotection and neuroregeneration for retinal diseases - Kitaoka, Yasushi; Harada, Takayuki; Nakazawa, Toru (Springer Japan, 2014)
This book provides the latest findings on neuroprotection and neuroregeneration as potential therapeutic strategies for various eye diseases, namely, glaucoma, age-related macular degeneration (AMD), retinal detachment, and retinitis pigmentosa. Glaucoma is one of the main causes of blindness throughout the world, and other diseases such as AMD and retinitis pigmentosa also lead to loss of vision. All these conditions are characterized by degeneration of specific retinal cell types, making it essential to establish treatments to protect retinal neurons and the optic nerve. With that aim in mind, this book explains the mechanisms underlying aforementioned diseases and their experimental models. The novel strategy proposals for the treatment of retinal diseases based on the concept of neuroprotection are also discussed in the main body of the text, while the section on regenerative research discusses optic nerve regeneration, endothelial progenitor cells, and iPS cells. This book is recommended as a professional reference work for all doctors and trainees in the field of ophthalmology who are interested in neuroprotective and neuroregenerative treatments.